Hubungan antara Tingkat Pendidikan Orangtua dengan Pengetahuan tentang Pelecehan Seksual pada Anak Remaja di Surakarta - Pritha Fajar Abrianti; Diffah Hanim; . Suparman (Nexus Kedokteran Komunitas, 2014)
Background: The incidence of sexual abuse in Indonesia increases every year. However, most cases of sexual abuse are often not revealed due to lack of knowledge. Based on the theory, education was one of the factors that affect knowledge of people or families. The aim of this study was to analyze association between parents education levels with knowledge about sexual abuse on adolescent. Methods: This study was an observational study with cross sectional design. This study used 76 samples of 7th grade students parents from two public junior high schools in Surakarta which was taken by cluster sampling. The level of parents education and knowledge were collected through a questionnaire. The association between parents education levels with knowledge was analyzed by Spearman Rho correlation test. Results: The number of 76 respondents, 11 respondents (14.5%) had low education level, 55 respondents (72.3%) had moderate education level, and 10 respondents (13.2%) had high education level. The distribution of respondents knowledge was 66 respondents (86.85%) had good knowledge, 9 respondents (11.85%) had sufficient knowledge, and 1 respondent (1.3%) had less knowledge. Spearman Rho analysis of test results obtained by the value of rs = 0.514 (p = 0.000) which meant that there were 51.4% parents education level have positive correlation with knowledge about sexual abuse on adolescent and 48.6% knowledge about sexual abuse on adolescent was influencedby another factors. This value indicated that there was moderate association between education levels with knowledge about sexual abuse on adolescent. Conclusion: The association between parents education level with knowledge about sexual abuse on adolescent in Surakarta was significant (p = 0.000, rs = 0.514). Keywords:Education level, Knowledge, Sexual abuse